(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
This is the era of modernization, science and technology development; resulted into more sedentary lifestyle. This era is more challenging because of lifestyle disorders which are due to change in dietary habits and mode of lifestyle. Obesity is one of the major lifestyle disorders which are a threat to life and is also a major cosmetic issue. Effective treatment for obesity is a need which is not available in the current scenario. In Ayurveda obesity can be correlated with Sthoulya or Medoroga. Acharya Charaka has prescribed Apatarpan chikitsa as the main Chikitsa for Sthoulya. The present article is about a case of Sthoulya treated by Apatarpan chikitsa mainly with Pachana, Udwartana, Swedana, Sadyavamana, Rukshana and Basti. Patients got significant relief in all the complaints and a remarkable weight loss in 21 days only.